A study of the effects of short-term AI coding course with gamification elements on students' cognitive mental health - KAMARUDIN, NURUL ALIN; Azman, Farah Nadia; Raja Ikram, Raja Rina; Syed Ahmad, Sharifah Sakinah; Zainuddin, Dzulfarqeish (UIKTEN - Association for Information Communication Technology Education and Science, 2022)
The objective of this research is to study the effect of short-term AI coding course with gamification elements on primary school students' cognitive skill and mental health. The proposed gamification coding activities was designed to help students in comprehending the coding concept, which is often seen as challenging. For 8 weeks, 43 primary school students aged 7 to 12 were randomly divided into a control group and an experimental group. The experimental group learnt AI and basic coding, whereas the control group just learned basic coding. According to the results, students' cognitive skills and mental health have improved.